Monism Versus Logical Pluralism in the Context of the Discussion between W.V.O. Quine and S. Haack - Czernecka-Rej, Bożena (Roczniki Filozoficzne, 2023)
One of the main questions in philosophy of logic is whether there is one logic or there are many logics. This question has been answered in many ways. Various answers have formed opposite standpoints: logical monism as against logical pluralism. Willard Van Orman Quine has been acknowledged as a representative of monism and Susan Haack — of pluralism. Both standpoints are maintained now: monism (e.g. Michael Dummett, Graham Priest, Timothy Williamson) or pluralism (e.g. Jc Beall and Greg Restall, Johan van Benthem, Ottavio Bueno and Scott Shalkovski, Stewart Shapiro and Roy Cook). Monism is significantly less preferred than pluralism. In this article, the sources of pluralism in logic have been indicated (among other things, ambiguity of connectives in the natural language, various understanding of truth and of logical consequence). Argumentations of some representatives of this standpoint have been presented.